THE SOCIAL-ECONOMIC CONDITION OF THE POPULATION RELOCATED TO THE LAND TO BE DEVELOPED AT THE INITIAL TIME (American Journal of Research in Humanities and Social Sciences, 2024)
This article talks about the initial socio-economic situation of the population relocated to the reserves and gray lands being developed in our republic, as well as the problems that arose in providing them with housing.